Estimating the mediating role of word of mouth between Bancassurance customer behavior and purchase intention - Iqbal, Muhammad Nawaz; Omercic, Jasmin; Bukhari, Muhammad Farhan (University of Loralai - Balochistan, 2024)
Existing literature rarely discuss about the factors influencing Bancassurance customer purchase intention via word of mouth. This research will explore the factors influence the purchase intention of Bancassurance customer through word of mouth. The rationale of this research is to drive policy implications for the Bancassurance system during product pitch and customer services and increase volume of Bancassurance customers. This study was conducted using a quantitative methodology. Survey questionnaire are used as an instrument to obtain participants response. The SEM Model mentioned above indicates that all out of six hypotheses, five were supported and one is rejected, which means the critical ratios in both cases should be greater than 1.96 and p-values lower than 0.05. Hence, it was found that WOM is the most important predictor of developing customer purchase intention for Bancassurance product distribution in Pakistan with customer perception, customer intention, customer trust, customer confidence taking second positions. It’s crucial for insurance companies to develop solutions that may satisfy a variety of needs because customers and prospects seek for products that are both worthwhile and affordable. Insurance companies have the chance to develop relationships with their clients through word-of-mouth marketing, which also enables them to produce additional business prospects.